Representation of Acehnese King Braveness In Pocut Muhammad Saga - Nia Liska Saputri; Yulia Sofiani; Irfan Hadi; Widiyarto, Sigit; Nana Suyana (Kirana Publisher (KNPub), 2023)
In this research, the researcher would like to analyze Aceh’s hikayat, titled Hikayat Pocut Muhammad, by Tengku Lam Rukam in the 18th century. The purpose of this study is to show the representation of the Acehnese people, especially among the kings through signifiers and signified. This research uses semiotics, as to show a representation of the existence and actions of Pocut Muhammad. The method is descriptive qualitative research. The data are words or sentences. that make up the meaning. For the technic, reading the hikayat and find the words, which can be considered as signifier and signified to find representation of Acehnese kings, depicted in Pacut Muhammad. As the results in this research are: 1) to prove that the signifier and signified are able to prove the representation of a character or problem. 2) Pocut Muhammad is a representation of the courage of the Acehnese kings in defending their land